Integrating Theory into Community Interventions to Reduce Liver Cancer Disparities: The Health Behavior Framework - Bastani, Roshan (2009)
Mitigating the unequal burden of cancer often involves conducting community-based trials to develop effective intervention strategies to promote cancer-related health behaviors. However, this is challenging due to the simultaneous influence of numerous factors, at multiple levels in the socio-ecological context, on health behavior. A sound conceptual framework can bring order to this complex environment and provide a roadmap for systematically addressing the multiple determinants of the behavior in question. This paper describes the application of The Health Behavior Framework, an integrative conceptual model, in an ongoing Program Project, “Liver Cancer Control Interventions for Asian-Americans.” The Framework has been integral to shaping all aspects of the three component research trials from selection of the study designs to development of the interventions and data collection instruments. We advocate universal adoption of theory into community-based intervention research as a way to accelerate our ability to develop effective interventions and facilitate synthesis of study results across populations and behavioral outcomes: critical steps in advancing the field of health disparities research.